Penggunaan Jenis Aromaterapi Dan Kebiasaan Merokok Berpengaruh Terhadap Perubahan Frekuensi Denyut Nadi Pada Supir: Efektivitas Penggunaan Aromaterapi terhadap Frekuensi Denyut Nadi pada Supir Bus - Fluorina Oryza Muslim; Santoso Santoso; Endang Purnawati Rahayu; Mitra Mitra; Nopriadi Nopriadi (STIKes Hang Tuah Pekanbaru, 2018)
The condition of sickness or health problems decreases the ability to work physically, being weak the sharpness of thinking to make quick and precise decisions, and decreases alertness and accuracy with the consequences of the worker concerned vulnerable to the occurrence of accidents This study aims to determine the relationship between aromatherapy type dominant to changes in pulse rate controlled by age variables, smoking habits, sleep duration, history of heart disease, fatigue, working hours of driver The research method using Quasy Experiment research design with non equivalent control group design is pre-test and post-test in experiment and control group with 40 samples taken by purposive sampling by considering inclusion criteria. The test used in this study is Paired T Test. The conclusion of this study is the using of aromatherapy does not affect the pulse. Type of giving atomatherapy , the time of giving is a factor confounding controlled.